Nile Tilapia Oreochromis niloticus Culture Development Strategy In Floating Net Cage Of Galela Lake, North Halmahera Regency, North Mollucas Province - Charlly N. Eteke; Hengky Sinjal; Edwin L. A. Ngangi; Suria Darwisito (Jurnal Ilmiah PLATAX, 2019)
This study aims to examine the development strategy of Nile tilapia (Oreochromis niloticus) culture in Galela Lake, North Halmahera Regency, North Mollucas Province. It is a descriptive study. Data collection used direct observations, interviews, and literature studies, and data analysis applied SWOT analysis, and continued with Quantitative Strategic Planning Matrix (QSPM)).  Results revealed that there were 6 priority strategies taken to develop the culture of the nile tilapia (O. niloticus) as follows: 1. Human resources development; 2. Take advantage of the investment-providing institutions for culture development; 3. Optimize the use of nile tilapia culture in the floating net cage; 4. Broaden the marketing access; 5. Increase the fish seed quality and the product quality; 6. Agreement among the fish farmers to maintain security in the floating net cage localities.Keywords: strategy, Galela Lake, nile tilapia, SWOT, QSPM. ABSTRAKPenelitian ini bertujuan untuk mengkaji strategi pengembangan budi daya ikan nila (Oreochromis niloticus) di Danau Galela Kabupaten Halmahera Utara Provinsi Maluku Utara. Penelitan ini merupakan penelitian deskriptif. Teknik pengembilan data melalui observasi langsung dan wawancara, dan studi literature. Analisis data menggunakan analisis SWOT. Dan dilanjutkan dengan uji OSPM  (Quantitative Strategis Planning Matrix).  Hasil dari analisis data menghasilkan enam strategi prioritas untuk pengembangan budi daya ikan nila (oreochromis niloticus) yaitu 1. Peningkatan pembinaan SDM 2. Memanfaatkan lembaga penyedia modal untuk pengembangan budi daya 3. Optimalisasi lahan budi daya ikan nila di karamba Jaring apung (KJA) 4. Memperluas akses pemasaran 5. Peningkatan kualitas benih ikan nila dan kualitas produk 6. Kesepakatan antar pembudidaya dalam menjaga keamanan di lokasi karamba jaring apung (KJA).Kata Kunci : Strategi, Danau Galela, Ikan Nila, Analisis SWOT, Analisis QSPM